Meta-Analysis of Student Reality Construction in Online Practicum - Yusmaniar Afifah Noor; Ngurah Made Darma Putra; Sunyoto Eko Nugroho (International Conference on Science, Education, and Technology, 2021)
The absence of ideal characteristics from the use of practicum can be solved based on empirical data which makes the practicum more effective. Reality construction is a way of taking pictures based on what students get from practical experience. The purpose of this study is to identify indicators of reality construction formed by students in online practicums. The method used is a meta-analysis by reviewing 24 international journals. The data analysis used is quantitative data analysis with effect size and percentage, while qualitative data analysis is for data resulting from narrative studies of the studies encountered. Based on analysis study of reality construction indicators can be generated five indicators that often appear, which is conceptual understanding, relevance and contribution of laboratory activities, student satisfaction, interaction and laboratory work patterns, resources and instructional. Students' conceptual understanding can be increased by applying online practicum. More than 60% of respondents stated that the contribution of online practicum is the same or better than conventional practicum. Overall, students feel quite satisfied in accessing online practicum, especially satisfaction in terms of time. However, students have more difficulty collaborating in online practicums. Along with the development of digital technology can facilitate interaction by communicating virtually. In addition, adequate quality of resources and instructional resources are needed so that they can effectively frame student learning.